2014
DOI: 10.1016/j.cell.2014.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and Type 2 Cytokine Signaling in Macrophages Orchestrate Development of Functional Beige Fat

Abstract: SUMMARY Beige fat, which expresses the thermogenic protein UCP1, provides a defense against cold and obesity. Although a cold environment is the physiologic stimulus for inducing beige fat in mice and humans, the events that lead from the sensing of cold to the development of beige fat remain poorly understood. Here, we identify the efferent beige fat thermogenic circuit, consisting of eosinophils, type 2 cytokines interleukin (IL)-4/13 and alternatively activated macrophages. Genetic loss of eosinophils or IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
723
7
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(784 citation statements)
references
References 54 publications
25
723
7
10
Order By: Relevance
“…While no changes were detected in the corticosterone levels (Figures S4A and S4B), the type 2 cytokines IL-4, IL-5, and IL-13 were markedly upregulated in both ingSAT and pgVAT of CR mice compared to the AL controls ( Figures 4A, S4C, and S4D). Eosinophils and the type 2 cytokines are sufficient to promote beige fat development through alternative activation of M2 macrophages expressing tyrosine hydroxylase (TH) (Ganeshan and Chawla, 2014;Lee et al, 2015;Martinez et al, 2009;Qiu et al, 2014), rate-limiting enzyme in the catecholamine biosynthesis (Nguyen et al, 2011). Indeed, Th mRNA and TH protein levels were increased in ingSAT and pgVAT in the CR mice ( Figures 4B and S4E).…”
Section: Decreased Caloric Uptake Enhances Type 2 Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…While no changes were detected in the corticosterone levels (Figures S4A and S4B), the type 2 cytokines IL-4, IL-5, and IL-13 were markedly upregulated in both ingSAT and pgVAT of CR mice compared to the AL controls ( Figures 4A, S4C, and S4D). Eosinophils and the type 2 cytokines are sufficient to promote beige fat development through alternative activation of M2 macrophages expressing tyrosine hydroxylase (TH) (Ganeshan and Chawla, 2014;Lee et al, 2015;Martinez et al, 2009;Qiu et al, 2014), rate-limiting enzyme in the catecholamine biosynthesis (Nguyen et al, 2011). Indeed, Th mRNA and TH protein levels were increased in ingSAT and pgVAT in the CR mice ( Figures 4B and S4E).…”
Section: Decreased Caloric Uptake Enhances Type 2 Immune Responsementioning
confidence: 99%
“…), both models showing impaired type 2 cytokine signaling (Lee et al, 2015;Qiu et al, 2014). The Il4ra À/À animals and their respective controls were on a BALB/c background, while the Stat6 À/À mice were on a C57BL/6J background.…”
Section: Type 2 Immune Signaling Is Necessary For the Browning And Mementioning
confidence: 99%
“…In this context, ATMs are the most intensively studied immune cells of the SVF. They have several functions in endocrine signaling by synthesizing hormones and adipokines that enable interference with insulin-controlled metabolism (Epelman et al 2014;Glass and Olefsky 2012;Lee and Lee 2014;Li et al 2013;Osborn and Olefsky 2012;Qiu et al 2014). The ATMs of the visceral adipose tissue, especially, have prime importance in metabolic regulation (Rosen and Spiegelman 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major differences is reliance on type 2 immunity for activation or not [68]. Qiu et al reported that cold exposure is accompanied by elevation of the Th2 cytokines (mainly interleukin 4 from eosinophils), which can readily engage M2 macrophage activation [68].…”
Section: Type 2 Immune Cytokines In Cold-stimulated White Adipose Tissuementioning
confidence: 99%